L2 writing and L2 written feedback in upper secondary schools as experienced by teachers - Manousou, Angeliki (2015)
L2 written feedback is a multi-faceted issue and this is the reason behind the big number of studies that have been conducted on it. However, the majority of studies deal with learners’ opinions of teachers’ feedback or several types of feedback and their advantages and disadvantages. There are no studies that could have addressed teachers’ opinions of their L2 written feedback. This study attempts to describe how L2 teachers view their written feedback on learners’ essays. In particular, it attempts to describe whether L2 writing is important nowadays and what text types learners produce. Moreover, it attempts to describe some definitions of feedback, forms of feedback, the effectiveness of feedback and whether feedback needs to be written in a milder way. Additionally, it attempts to describe learners’ responsibility for processing teachers’ feedback, the focus of feedback, its handling in class and whether teachers follow written guidelines when giving feedback. The data includes six recorded interviews of L2 teachers in upper secondary schools in Finland and in Greece. In particular, three teachers are Finnish and three teachers are Greek. The results of this study reveal that L2 teachers have their own reasons for making choices when giving feedback. They reflect and give explanations on their choices and they recognise their errors when giving feedback. In general, they have their own opinion about how feedback should be given to learners.